Strategi Pengembangan Usaha Kecil Dan Mikro Serta Dampaknya Bagi Kesejahteraan Masyarakat Di Desa Kweden Kecamatan Tarik Kabupaten Sidoarjo (Menurut Pandangan Maqashid Syariah) - Faizah Laila Maulidah; Renny Oktafia (Jurnal Ilmiah Ekonomi Islam, 2020)
With the development of the times, many small and medium enterprises have sprung up, because by establishing these small and medium enterprises will increse income and help the surrounding community. So that this bussiness will have an impact on the welfare of the community. The purpose of this research is to find out how the implementation of the development strategy and the impact of the implementation of the development strategy for small and micro enterprises in Kweden Village, Tarik Dictrict, Sidoarjo Regency. The type of research used in this research is qualitative research methods and the approach of this research is a acse study approach. The results of this study, it can be concluded that the implementation of the development strategy and the impact of the implementation of the development strategy of micro and small enterprises in Kweden Village is quite good. This is proven by the development of this business being able to recriut employees, especially the community around Kweden Village, which has a very positive impact with the existence of this snack business, which can reduce the level the level of unemployment.